Stroke frequency strategies of international and national swimmers in 100m races - Kjendlie, P. L.; Haljand, R.; Fjoertoft, O.; Stallman, R. K. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to examine stroke rate strategies of elite international and national junior level swimmers. Norwegian junior national (NOR) and European Short course championships (EUR) race analysis was performed by videography. Clean swimming velocity (Vclean) stroke rate (SR) and stroke length (SL) were analyzed for each lap. The frequency of use of five models for SR strategies during a race were identifled for finalists (rank 4th - 6th/8th) and the top 3 performers for all 100m races. The most common strategy was model D for the top 3 performers (decreasing SR at the beginning, and increasing SR in the end of the race) and model B (decreasing SR throughout the race) for the finalists. It seems that the strategies most often used by the best performers in 100m short course races are decreasing during the first part of the race, and increasing at the end, and is a compensatory mechanism for a decrease in SL.